Defoliation by Gypsy Moth (Lepidoptera, Erebidae) Induces Differential Delayed Induction of Trichomes in Two Birch Species. Issue 2 (18th December 2020) - Matsuki, Sawako; Toki, Rika; Watanabe, Yoko; Masaka, Kazuhiko
Abstract: Outbreaks of the gypsy moth ( Lymantria dispar japonica Motschulsky) cause serious defoliation in birch. A single year of defoliation has no significant impact on the trees, whereas continuous defoliation events could be fatal. How birch species avoid serious damage caused by gypsy moth outbreak is yet to be revealed. Trichomes on leaf surfaces of birch trees are an effective antiherbivore defense strategy. We examined a 1-yr delayed induction of glandular (GT) and nonglandular trichomes (NGT) on leaf surfaces caused by stress in white birch ( Betula platyphylla Sukaczev var. japonica [Miq.] Hara) and monarch birch ( Betula maximowicziana Regel). Saplings were subjected to four treatments in June 2009: herbivory (50% of the leaf area was grazed by gypsy moths), mechanical cutting (50% of the leaf area was cut using scissors), shading (50% light shading with a black sheet), and control (covered with a net to prevent herbivory). Then, the density of GT and NGT on early leaves was determined in April 2010. In both birch species, the density of GT was higher in herbivory than in other treatments. The density of GT due to mechanical cutting was higher than that in the control, but only for white birch. However, the density of NGT was lower after mechanical cutting than in other treatments for white birch. There were no differences in the density of NGT among treatments for monarch birch. These results show that 1-yr delayed induction of GT by herbivory was stronger in white birch than in monarch birch.